A single closed-loop kinematic chain approach for a hybrid control of two cooperating arms with a passive joint: An application to sawing task - Yeo, HJ; Suh, IH; Yi, BJ; Oh, SR (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1999)
This work deals with a sawing task performed by two cooperating arms. The two-arm system under our hand consists of a four degree-of-freedom (DOF) SCARA robot and a five DOF PT200V robot. When the two arms are rigidly grasping a saw, the mobility of the system is three, which is not enough for sawing tasks, Therefore, we deliberately insert a passive joint at the end of the SCARA robot to increase the mobility up to four. A hybrid control method to regulate the force and velocity by the two arms is proposed in this work. The proposed scheme has three typical features; first, the two arms are treated as one arm in a kinematic viewpoint, Secondly, our approach is different from other acceleration-based approach, in the sense that our hybrid control method is based on a Jacobian and an internal kinematics for a single closed-kinematic chain of the two arms to reflect the nature of the position-controlled industrial manipulator, Thirdly, the proposed scheme is not only able to operate the system even if a passive joint exists, but also is able to utilize the internal loads for useful applications such as pitch motion control. We experimentally show that the performance of the velocity and force response are satisfactory, and that one additional passive joint not only prevents the system from unwanted roll motion in the sawing task, but also allows an unwanted pitch motion to be notably reduced by an internal load control, To show the effectiveness of the proposed algorithms, we perform experimentation under several, different conditions for saw, such as three saw blades, two sawing speeds, and two vertical forces.
Keywords: FORCE CONTROL; ROBOT MANIPULATORS; MOTION; STIFFNESS